Maintaining or Abandoning African Rice: Lessons for Understanding Processes of Seed Innovation - Teeken, Béla; Nuijten, E.; Temudo, M.P.; Okry, F.; Mokuwa, A.; Struik, P.C.; Richards, P. (Springer, 2012)
Rice breeding and crop research predominantly emphasize adaptation to ecological conditions. Based on qualitative and quantitative research conducted between 2000 and 2012 we show how ecological factors, combined with socioeconomic variables, cultural norms and values, shape the use and development of local technologies related to the cultivation of African rice (Oryza glaberrima Steud.) in seven West African countries (Ghana, Guinea, Guinea-Bissau, Senegal, Sierra Leone, The Gambia and Togo). In this region the role of African rice is diverse across ethnic groups. Findings suggest that farmers, through various pathways, are active in the development of promising new varieties based on genetic resources of Asian rice, African rice, or both, as well as in the adoption of modern varieties. These findings require further research into interactions among ecological, genetic, socioeconomic and cultural factors within farmers' innovation systems and recognition of emergent knowledge and technologies resulting from such interactions